Hamka and Islam cosmopolitan reform in the Malay world - Aljunied, Syed Muhd. Khairudin 1976- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2018)
"Examines Hamka's project of cosmopolitan reform in his effort to reconstruct the ways in which Islam was understood and practiced in Malay world"--